Liposome-Encapsulated Berberine Alleviates Liver Injury in Type 2 Diabetes via Promoting AMPK/mTOR-Mediated Autophagy and Reducing ER Stress: Morphometric and Immunohistochemical Scoring - Safaa I. Khater; Taghreed N. Almanaa; Doaa M. Abdel Fattah; Tarek Khamis; Mona M. Seif; Naief Dahran; Leena S. Alqahtani; Mohamed M. M. Metwally; Mahmoud Mostafa; Raghad A. Albedair; Azza I. Helal; Manal Alosaimi; et al. (MDPI AG, 2023)
In the advanced stages of type 2 diabetes mellitus (T2DM), diabetic liver damage is a common complication that can devastate a patient's quality of life. The present study investigated the ability of liposomal berberine (Lip-BBR) to aid in ameliorating hepatic damage and steatosis, insulin homeostasis, and regulating lipid metabolism in type 2 diabetes (T2DM) and the possible pathways by which it does so. Liver tissue microarchitectures and immunohistochemical staining were applied during the study. The rats were divided into a control non-diabetic group and four diabetic groups, which are the T2DM, T2DM-Lip-BBR (10 mg/kg b.wt), T2DM-Vildagliptin (Vild) (10 mg/kg b.wt), and T2DM-BBR-Vild (10 mg/kg b.wt + Vild (5 mg/kg b.wt) groups. The findings demonstrated that Lip-BBR treatment could restore liver tissue microarchitectures, reduce steatosis and liver function, and regulate lipid metabolism. Moreover, Lip-BBR treatment promoted autophagy via the activation of LC3-II and Bclin-1 proteins and activated the AMPK/mTOR pathway in the liver tissue of T2DM rats. Lip-BBR also activated the GLP-1 expression, which stimulated insulin biosynthesis. It decreased the endoplasmic reticulum stress by limiting the CHOP, JNK expression, oxidative stress, and inflammation. Collectively, Lip-BBR ameliorated diabetic liver injury in a T2DM rat model with its promotion activity of AMPK/mTOR-mediated autophagy and limiting ER stress.